Pengaruh Virtual Learning Pembelajaran Jarah Jauh Guru Pendidikan Agama Islam dan Partisipasi Orang Tua terhadap Hasil Belajar PAI - Heny Trikusuma Hidayati; A. Dardiri Hasyim (Fahima, 2022)
This study aims to determine the effect of virtual learning on Islamic Religious Education learning outcomes, the effect of parental participation on Islamic Religious Education learning outcomes, as well as the effect of virtual learning and parental participation on PAI learning outcomes at SMPN 4 Karanganyar academic year 2020/2021. The hypothesis proposed is that virtual learning and parental participation have a significant effect on PAI learning outcomes for class VIII SMPN 4 Karanganyar academic year 2020/2021. This research is quantitative descriptive with data collection methods are questionnaires, observations, interviews and documentation. Subjects were taken by class VIII SMPN 4 Karanganyar with a population of 360 and a sample of 100 students. Data analysis used preliminary analysis, hypothesis testing and further analysis. The results showed that the effect of virtual learning on PAI learning outcomes was in good category, the influence of parental participation on PAI learning outcomes was in good criteria, and the influence of virtual learning and parental participation had a significant effect on PAI learning outcomes for class VIII students of SMPN 4 Karanganyar academix year 2020/2021 which is in the good category.